Parachute-Like Mitral Valve Tuberculoma: A Rare Presentation - Arslan Masood; Gul Zaman Khan; Irfan Bashir; Zubair Akram (Case Reports in Cardiology)
There have been anecdotal reports of tuberculous cardiac involvement, mainly in cases of military tuberculosis or immune deficient individuals. The spectrum of clinical presentations of tuberculous cardiac involvements includes incidental detection of single and multiple well-circumscribed tuberculomas, symptomatic obstructive lesions, AV conduction abnormalities, and even sudden death. We present a case of cardiac tuberculoma in an immune-competent person who presented with worsening dyspnea. The unique morphology of this mass posed an imaging challenge that required 4-dimensional (4D) echocardiography and cardiac magnetic resonance (CMR) detail to differentiate the mass from an anterior mitral leaflet (AML) aneurysm. Histological examination after surgical resection confirmed its tuberculous etiology.